The influence of training on neuromuscular factors in elite and non elite fencers - Tsolakis, C.; Tsiganos, G. (Serbian Journal of Sports Sciences, 2008)
The aim of this study was to investigate the influence of training on neuromuscular factors related to the speed of basic kinetic fencing patterns. 10 elite and 10 non-elite fencers underwent: a) anthropometric measurements and leg cross sectional area estimation (leg CSA), b) determination of jumping ability and the time needed to perform a lunge attack, using 7 tests on a jumping mat (Ergojump system): squat jump (SJ), counter-movement jump (CMJ), countermovement jump on the dominant and non-dominant leg (CMJD-ND), counter-movement jump using the hands (CMJH), drop jump (DJ), and lunge. Elite fencers were significantly stronger in CMJD and CMJND (23-16%, p<0.01-0.000) than non-elite fencers. Significant differences in leg CSA and explosive strength (10-15%, p<0.005-0.000) were observed between the dominant and non-dominant limp of fencers. Smaller significant differences (8%, p<0.000) were observed in leg CSA of non-elite fencers. There was no relationship between muscular and strength asymmetries. The time needed to perform a lunge attack was similar among the elite and non-elite fencers and was negatively related to muscle elasticity of elite fencers (0.71, p<0.05). Fencing training produces significant muscular and strength asymmetries, which are not related to each other, and the fencers` muscle elasticity seems to be an important factor in neuromuscular performance among fencers of different technical level.